Histological Effect of Ursolic Acid, Hyperinsulinemia and Vitamin B Complex on Sciatic Nerve Repair and Lipid Profile of Alloxan induced Diabetic Rabbits (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This study aimed to evaluate the effects of ursolic acid, hyperinsulinemia and vitamin B complex on sciatic nerve repair in diabetes mellitus male rabbits, determination of their effects on lipid profile and histological structures of the sciatic nerve. The results of  our study showed that alloxan induced diabetes caused a significant increase (p